Operating system concepts - Silberschatz, Abraham (Addison Wesley Longman, 1998)
This best-selling book, now in its fifth edition, provides a solid theoretical foundation for understanding operating systems. Authors Abraham Silberschatz and Peter Galvin discuss key concepts that are applicable to a variety of systems. They also present a large number of examples taken from common operating systems, including WindowsNT and Solaris 2. This book teaches general principles in operating systems while giving the teacher and students the flexibility to choose the implementation system.